Kualitas Implementasi Kurikulum dalam Pembelajaran - Abduloh Abduloh (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2019)
The development of science and technology, at the moment is increasingly rapid. Therefore the world of education must be able to adapt it to the learning process, namely by implementing a curriculum to determine the quantity and quality of education outcomes, the good and bad results of education depend on "Quality of curriculum implementation", the most important thing in curriculum implementation is the quantity and quality of the learning process. To obtain relevant information data in this study, using the method of quality concept analysis The implementation of the curriculum in learning inquiry concepts through theoretical analysis. Researchers identify, study and then synthesize research data to gain an understanding of the quality of curriculum implementation in learning that can be directly observed. Research data was collected through literature studies of various theoretical documents. The researcher interprets the data and facts to obtain an explanation of the concept of curriculum implementation in learning. The writing of this article aims to examine the concept of curriculum implementation in effective, efficient and productive learning in achieving the learning objectives set in the curriculum. Achieving learning objectives can be supported by the roles and functions of professionalism of teachers/educators in determining and implementing: 1) Implementation of the curriculum in learning with activities include: planning, implementing, evaluating and improving learning that is useful for increasing the quantity and quality of learning objectives. 2) The process of implementing the curriculum in learning is in accordance with the goals and achievements set by using various approaches / models, media, methods, techniques, and learning strategies and managing the learning process in the classroom and outside the classroom efficiently. 3) Learning outcomes that oriented to the quantity and quality of repairs can solve various problems.